QINGDAI (QD) FOR PATIENTS WITH ACTIVE ULCERATIVE COLITIS: A RETROSPECTIVE ISRAELI NATIONAL EXPERIENCE. (26th January 2023) - Kopylov, Uri; Salomon, Nir; Zittan, Eran; Lahat, Adi; Eliakim, Rami; Weiss, Batia; Koslowsky, Benjamin; Gil, Ariella Shitrit-Bar; Saban, Lotem; Maharshak, Nitsan; Hirsch, Ayal; Ritter, Einat; et al.
Abstract: BACKGROUND: QingDai (QD, Indigo) was shown to be effective for ulcerative colitis (UC) in randomized controlled trials and retrospective reports from Japan. However, experience with QD for UC in the West is extremely limited. We aimed to describe the effectiveness and safety of QD in a national cohort of patients with UC followed at tertiary referral centers in Israel. METHODS: A retrospective study. We included adult patients who received QD for active UC (simple colitis clinical activity index (SCCAI)≥3) between 2018 -2022 at five academic centers. A majority of patients received QD in a combination with curcumin (CurQD). The primary outcome was clinical response at the end of induction (defined as the last follow-up visit between weeks 8 to 16 from the start of the treatment). Clinical response was defined as an improvement of SCCAI≥ 3 points; clinical remission as SCCAI≤2. C-reactive protein (CRP), fecal calprotectin (FC) levels and endoscopic Mayo score before and after treatment were compared when available. Starting corticosteroid or biologic treatment, hospitalization due to disease exacerbation, colectomy, discontinuation of treatment due to an adverse event or missing follow-up data were considered treatment failures RESULTS: A total of 82 patients were included [median age-32, interquartile ratio (IQR)-23-41), 47 (57.3%) female; disease extent- 16 (20.5%)-proctitis, 28 (35.9%)- left-sided, 34 (43.6%) – pancolitis]. At treatment onset, 27 (41.5%) were treated with corticosteroids and 28 (34.1%) with a biologic or small molecule, 10 (12.9%) failed ≥ 3 biologics or small molecules. Median SCCAI was 6 (5-9), CRP- 5 (2-17) mg/L, fecal calprotectin levels – 698 (320 -1190) mg/g and endoscopic Mayo score- 2. QD was initiated in combination with curcumin (CurQD) in 77 (95.1%) of the patients. The last induction follow-up occurred after a median of 8 (8-12) weeks. At the end of induction, 64 (78%) responded to treatment, including 52 (63.4%) that achieved clinical remission (figure 1). At the end of induction, median SCCAI was 2 (1-3) (p<0.001), CRP- 2 (1-5) mg/L (p=0.003, 22 patients with paired measurements), FC levels -75 (12-139, 35 patients) mg/g (p<0.001, Figure 2) and median endoscopic Mayo score -1 (0-2) (p=0.03, 12 patients). Two (2.3%) patients experienced headaches and 5 (6.1%) mild liver function elevations that resolved spontaneously or following QD discontinuation (2 patients). CONCLUSIONS: In this multicenter retrospective cohort study, QD treatment (predominantly as combination CurQD) was effective for induction of clinical response and remission in active UC patients, including biologic-experienced patients. All adverse events were mild and resolved either spontaneously or after QD discontinuation. Our results suggest QD as a potential effective and safe agent for induction of response and remission in patients with active UC.